The hourglass factory - Ribchester, Lucy (Pegasus Crime, an imprint of Pegasus Books LLC, 2016)
"London, 1912. The suffragette movement is reaching a fever pitch, and Inspector Frederick Primrose is hunting a murderer on his beat. Across town, Fleet Street reporter Frances “Frankie” George is chasing an interview with trapeze artist Ebony Diamond. Frankie finds herself fascinated by the tightly-laced acrobat and follows her to a Bond Street corset shop that seems to be hiding secrets of its own. When Ebony Diamond mysteriously disappears in the middle of a performance, Frankie and Primrose are both drawn into the shadowy world of a secret society with ties to both London's criminal underworld and its glittering socialites."--From book jacket.